Scheduling a Full-Time Workforce to Meet Cyclic Staffing Requirements - Baker, Kenneth R. (Management Science, 1974)
A simple algorithm is developed for the problem of assigning days off to full-time staff given a cyclic seven-day demand pattern. The formulation assumes that employees are entitled to two consecutive days off each week and that the objective is to find a minimum staff size capable of meeting the requirements. The algorithm involves only hand calculations, and its computing effort is predictable.